Evaluation of directivity for planar antenna arrays. - Min Joon Lee (IEEE Antennas & propagation magazine.)
In this paper, the directivity, including phase shift factors, for several types of uniformly excited planar arrays is obtained. Four types of dipole arrays are considered: arrays of collinear short dipoles, and of parallel short dipoles; and broadside and end-fire arrays of crosses of short dipoles. Curves of directivity versus inter-element spacing and scan angle for planar arrays with these element power patterns are presented.